Efektifitas Dan Efisiensi Pengelolaan Alokasi Dana Desa Dalam Meningkatkan Pembangunan Fisik Di Desa Loleo Jaya Kecamatan Morotai Utara Kabupaten Pulau Morotai - Nurhikmah Sibua; Grandi Silva Lestari Forno (Jurnal Akuntan Publik, 2023)
The purpose of this study was to determine the effectiveness and efficiency of managing village fund allocations in increasing physical development in Loleo Jaya Village, Morotai District, North Morotai Island Regency. The type of research used is descriptive qualitative analysis. Collecting qualitative descriptive analysis data utilizing observation, documentation and interviews. Data in the form of village fund realization reports were taken in Loleo Jaya Village, North Morotai District, Morotai Island Regency. The purpose of the analysis is to find out that the management of village fund allocations has been effective, to know that the management of village fund allocations has been efficient, and to find out what factors influence the effectiveness and efficiency of village fund allocations. The results of this study are Loleo Jaya Village, North Morotai District, Morotai Island Regency for the last three years. Analysis of the effectiveness ratio of village funds from 2020 was 137.02%, in 2021 was 101.09% and in 2022 was 104.75% meaning budget absorption for the last three years has met the performance criteria for the effectiveness of village funds very well. Analysis of the efficiency ratio of village funds from 2020 (73.86%) is not efficient, 2021 (98.11%) is not efficient, and 2022 (38.00%) is less efficient, meaning that the absorption of the village budget from the last three years has not been maximized according to the criteria performance is still lacking efficiency. There are 3 factors inhibiting effectiveness and efficiency in allocating village funds in Loleo Jaya Village, North Morotai District, namely: 1. Delays in disbursing village funds, 2. Lack of quality human resources, 3. Lazy culture and lack of community participation.